Meningkatkan Aktivitas dan Keterampilan Berpikir Kritis Muatan Matematika menggunakan Model Bersama di Kelas 5 Sekolah Dasar - Winanda, Rahma; Maimunah, Maimunah (Lembaga Yasin AlSys, 2025)
This study is motivated by the low levels of student engagement, critical thinking skills, and learning outcomes in Mathematics among fifth-grade students at SDN Belitung Selatan 2 Banjarmasin. These issues stem from students’ limited critical thinking abilities, low participation during lessons, and the use of instructional methods that are neither engaging nor enjoyable. To address these challenges, the BERSAMA learning model was implemented. The objectives of this research are to: (1) improve students’ learning activity; (2) enhance critical thinking skills; and (3) analyze learning outcomes following the application of the BERSAMA model. A qualitative approach was employed using Classroom Action Research (CAR), conducted over four sessions. The study involved 20 students during the second semester of the 2024/2025 academic year. Data were collected through observations of teacher and student activity, assessments of students' critical thinking skills, and both individual and group learning outcomes tests. Data were analyzed using qualitative descriptive techniques and presented in tables and graphs with percentages. The results showed significant improvement: teacher activity scores increased from 21 (“Good”) to 27 (“Very Good”); student activity rose from 50% (“Few Students Active”) to 100% (“All Students Highly Active”); critical thinking skills improved from 45% (“Few Students Skilled”) to 100% (“All Students Highly Skilled”); and learning mastery increased from 40% (“Few Students Performed Well”) to 90% (“Most Students Performed Very Well”). The study concludes that the BERSAMA model is effective in enhancing teacher and student activity, critical thinking skills, and learning outcomes in Mathematics. The findings recommend the BERSAMA model as an innovative teaching strategy for teachers, school administrators, and elementary education researchers.